A Analisis Penerapan Kompetensi Guru PAUD di TK Al-Husna Pekanbaru: Kompetensi Pedagogik, Kompetensi Profesional, Kompetensi Sosial, Kompetensi Kepribadian - Aprianti, Desi; Jihan Febria Novianti; Tanjung, Novita; Rita Kurnia, Rita Kurnia; Asfi Yanti WE, Asfi Yanti WE (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
This study aims to analyze the implementation of four main competencies of Early Childhood Education teachers, which include pedagogical, professional, social, and personal competencies at Al-Husna Kindergarten, Pekanbaru. This study employs a qualitative, descriptive approach, focusing on in-depth reporting of teachers’ actual practices in daily learning activities. Data were gathered using observation, interviews, and documentation. The collected data were then analyzed using qualitative analysis procedures, including data reduction, data presentation, and conclusion drawing, providing a comprehensive depiction of teachers’ abilities in carrying out their professional responsibilities. The research subject consisted of four experienced Kindergarten B teachers at Al-Husna Kindergarten, Pekanbaru, who were actively involved throughout the instructional process. The results showed that teachers at Al-Husna Kindergarten had implemented pedagogical competence well. This was demonstrated through their ability to design Daily Learning Implementation Plans, manage classes effectively, and create a fun and interactive learning atmosphere. Professional competence is reflected in mastery of teaching materials, the ability to manage an educational play environment, the application of reflection to improve educational quality, and participation in self-development activities such as training and workshops. Social competence is evident in teachers’ ability to communicate and collaborate harmoniously with students, colleagues, and parents. However, strengthening personal competence is still necessary so that teachers can serve as patient, authoritative, and high-integrity role models in carrying out their roles as Early Childhood Education students.